Kesiapsiagaan Generasi Z terhadap Bencana Geologi akibat Aktivitas Sesar Lembang di Wilayah Bandung - Tasya Rahmadhani; Armi Susandi; Heridadi Heridadi (Lembaga Yasin AlSys, 2025)
The limited research on knowledge, risk perception, and preparedness of Generation Z regarding geological disaster threats in the Bandung area forms the background of this study, considering the potential of the Lembang Fault to cause significant social and economic impacts in densely populated urban regions. This research aims to explore and understand the levels of knowledge, risk perception, and preparedness behaviors of Generation Z in facing potential geological disasters. A descriptive qualitative approach was adopted, with informants selected through purposive sampling based on the criteria of individuals born between 1997 and 2010 residing in Bandung City and Regency. Data were collected through semi-structured in-depth interviews and analyzed using the Miles, Huberman, and Saldaña model, which includes data reduction, data display, and verification. The findings reveal that while most Generation Z participants possess basic knowledge about the Lembang Fault and recognize earthquakes as its primary consequence, this awareness is not yet reflected in practical preparedness measures. Limited participation in evacuation drills, absence of personal emergency plans, and restricted access to disaster-related information are identified as major obstacles. The study concludes that there is a gap between knowledge and preparedness actions among Generation Z. Therefore, an integrated strategy involving digital-based disaster education, participatory training, and the strengthening of local community networks is necessary to enable Generation Z to become strategic actors in building disaster resilience in high-risk areas such as Bandung.